Synergistic response of steel columns to explosive thermal and long duration blast loading. (15th October 2021) - Clough, Laurence G.; Clubley, Simon K.
Highlights: Thermo-mechanical response of steel plates within an explosive fireball. Response of steel columns subject to thermal and long duration blast loads. Numerical analysis of steel columns under thermal and long duration blast loads. Parametric study of steel columns under thermal and long duration blast loads. Abstract: This paper investigates the response of steel columns to combined pre-cursor thermal and long duration blast loads. Blast waves are the primary damage mechanism from explosive events. However, explosive events also emit thermal loads. Depending upon the explosive size and standoff distance, the effective thermal load can reach a structure prior to the arrival of the blast. An effective thermal load can damage steel structures such that total damage from the combined thermal and blast load is different to, or greater than the blast load alone. There is limited research to date investigating the synergistic response of steel structures to explosive thermal and blast loading. This paper specifically focuses on the numerical and computational methods appropriate to predict the response of steel columns subject to focused thermal and long duration blast loads (positive pressure phase exceeding 100 ms). Results from a substantive study are presented, showing a synergistic response within a sensitivity envelope of load cases. Computational methods are verified with a novel series of explosive fireball trials and a series of combined thermal, compression and long duration blast trials.